Microbial-Based Technologies for Improving Smallholder Agriculture in the Ecuadorian Andes: Current Situation, Challenges, and Prospects - Yarzábal, Luis Andrés; Chica, Eduardo J. (Frontiers in Sustainable Food Systems, 2021)
As in other Andean countries, smallholder agriculture is the base that supports food and nutrient security in Ecuador. Ironically, in spite of their importance, the development of context-appropriate technologies for these farming systems remains still at its infancy. Today, most smallholders in the Ecuadorian Andes practice a type of hybrid agriculture that merges traditional local practices and modern technologies. This mixture of traditional and “modern” conventional technologies does not always result in resource-efficient sustainable practices. Although they represent only part of a global solution, microbial-based technologies offer a great potential to improve the functioning of smallholder farms in the Ecuadorian Andes. From nutrient cycling to biocontrol and plant growth promotion, microbial technology applications match existing needs for technology development in these systems; however, as in many cases, knowledge gaps and context-adapted implementation are some of the challenges that slow down the spreading and efficient use of these technologies. Here we offer a review of the efforts made as of today to characterize, develop and test microbial-based technologies that could boost smallholder Andean agriculture with a particular focus in the Ecuadorian context. We also propose potential lines of action to increase or accelerate the impact of these technologies.